Kajian Kriminologis terhadap Modus Penipuan melalui Transfer Uang pada Agen Bank Rakyat Indonesia (BRI) Link di Kabupetan Kupang - Fransisco Juliano Joseph De Kurnia Bansae; Debi F. Ng. Fallo; Deddy R. Ch. Manafe (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to examine criminologically the modus operandi and causal factors of fraud committed through money transfer transactions at BRILink agents in Kupang Regency. The research employed an empirical juridical method with a criminological approach. Data were collected through interviews, literature studies, and documentation, and were analyzed using descriptive qualitative methods. The findings reveal that the offender exploited a close personal relationship and the victim’s trust to facilitate the fraudulent act. The modus operandi involved manipulating the BRImo mobile banking application display and falsifying transfer receipts, leading the victim to believe that the transaction had been successfully completed and subsequently hand over cash. The factors contributing to the crime consist of internal factors, including economic motives, the desire to obtain money quickly, and abuse of trust, as well as external factors such as the close relationship between the offender and the victim, the ease of digital technology utilization, and the victim’s vulnerability in transaction verification. The study highlights the importance of enhancing vigilance, transaction verification procedures, and supervision of digital banking services to prevent similar crimes.